The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.21236/ada535421
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Training Considerations for Use in Simulation-Based Systems

Abstract: Public reporting burden for this collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching data sources, gathering and maintaining the data needed, and completing and reviewing the collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing this burden to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…A similar goal is desired in serious games, however, this incorporates the additional requirement of ensuring effective learning content delivery. DDA is explored in a serious games context to adapt the serious game to the needs of the learner and ultimately achieve better learning outcomes (Landsberg et al, 2010). Striking the right balance of challenge is critical to maximizing the chance of positive learning outcomes by both engaging the learner and helping achieve a Flow state (Hamari et al, 2016), or similar positive motivational or affective states.…”
Section: Introductionmentioning
confidence: 99%
“…A similar goal is desired in serious games, however, this incorporates the additional requirement of ensuring effective learning content delivery. DDA is explored in a serious games context to adapt the serious game to the needs of the learner and ultimately achieve better learning outcomes (Landsberg et al, 2010). Striking the right balance of challenge is critical to maximizing the chance of positive learning outcomes by both engaging the learner and helping achieve a Flow state (Hamari et al, 2016), or similar positive motivational or affective states.…”
Section: Introductionmentioning
confidence: 99%
“…Acquisition of psychomotor skills can be achieved by simulation training, a process through which actions are imitated and exercised in controlled environments with the intention of applying the skills to real-life scenarios [ 7 ]. However, simulator training time is still very expensive and in some cases is a rare commodity which must derive the most benefit possible with minimal use of special resources [ 8 , 9 , 10 ]. State-of-the-art innovative methods are applied to simulators in various fields in order to improve learning and training [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Adaptive training (AT) is training that adjusts relative to a learner's performance, aptitude, or learning preference (Landsberg, Van Buskirk, Astwood, Mercado, & Aakre, 2011). Several literature reviews have found that AT generally leads to positive learning outcomes (e.g., Durlach & Ray, 2011;Landsberg et al, 2011;McCarthy, 2008), but the AT literature lacks systematic empirical evidence to determine which AT techniques work best for which tasks and learners (Durlach & Ray, 2011;Vandewaetere, Desmet, & Clarebout, 2011). Therefore, the goal of the present experiment was to determine if similar AT techniques that were effective in one type of task would also be effective for a different task.…”
mentioning
confidence: 99%